EG allocation and sizing using real coded genetic algorithm method to minimize losses and improve voltage profile - Mohd Herwan, Sulaiman; Omar, Aliman; Siti Rafidah, Abdul Rahim; Mohd Rafi, Adzman (Universiti Teknikal Malaysia Melaka (UTeM), 2011)
The 2nd International Conference on Engineering and ICT 2010 (ICEI 2010) organized by Universiti Teknikal Malaysia Melaka (UTeM), 18th - 20th February 2010 at Holiday Inn, Melaka, Malaysia.